1996
DOI: 10.1074/jbc.271.15.8925
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a Major Peritrophic Membrane Protein, Peritrophin-44, from the Larvae of Lucilia cuprina

Abstract: The peritrophic membrane is a semi-permeable chitinous matrix lining the gut of most insects and is thought to have important roles in the maintenance of insect gut structure, facilitation of digestion, and protection from invasion by microrganisms and parasites. Proteins are integral components of this matrix, although the structures and functions of these proteins have not been characterized in any detail. The peritrophic membrane from the larvae of the fly Lucilia cuprina, the primary agent of cutaneous myi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
131
1
3

Year Published

2000
2000
2011
2011

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 172 publications
(141 citation statements)
references
References 44 publications
6
131
1
3
Order By: Relevance
“…5, lanes 2 and 4). Strongly bound PM proteins were also observed in Trichoplusia ni (Lepidoptera) larvae (Wang & Granados 2000) and Lucilia cuprina (Diptera) larvae (Elvin et al 1996). The majority of the total PM proteins from L. cuprina are not solubilized by strong denaturants such as SDS used in our experiments (Tellam et al 1999).…”
Section: Resultsmentioning
confidence: 71%
See 1 more Smart Citation
“…5, lanes 2 and 4). Strongly bound PM proteins were also observed in Trichoplusia ni (Lepidoptera) larvae (Wang & Granados 2000) and Lucilia cuprina (Diptera) larvae (Elvin et al 1996). The majority of the total PM proteins from L. cuprina are not solubilized by strong denaturants such as SDS used in our experiments (Tellam et al 1999).…”
Section: Resultsmentioning
confidence: 71%
“…In order to verify whether the D. urucu root bark extract treatment could also interfere in the interaction of PM and its associated proteins, two buffers were sequentially employed to extract PM proteins according to Elvin et al (1996). Ae.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, we only present one K D for (GlcNAc) 6 , but this K D ITC is only an apparent value. Trp fluorescence quenching experiments have also been reported for peritrophin-44, a CBM14 lectin containing four ChBD repeats (8). In this case, Trp fluorescence quenching was ϳ16% at full saturation for (GlcNAc) 3 , whereas peritrophin-44 only contains one Trp residue in one of the four CBM14 repeats.…”
Section: Table IImentioning
confidence: 58%
“…(14), Penaeus japonica chitinase 1 (Pj-chit1) (27), Chelonus sp. chitinase (Ch-chit) (28), 44-kDa glycoprotein from Lucilia cuprina (Peritrophin-44) (13), and Trichoplusia ni intestinal mucin (Tn-IM) (29). Plants are as follows: hevein from rubber tree (Hevein) (9), Amaranthus caudatus antimicrobial protein 2 (Ac-AMP2) (10), and four homologous domains of wheat germ agglutinin (WGA A, -B, -C, and -D) (11).…”
Section: Nmr Structure Of the Invertebrate Chitin-binding Protein 179mentioning
confidence: 99%
“…It has been well demonstrated that this domain is indispensable for the antimicrobial activity and exhibits a significant conservation in primary sequence (Ͼ40%) and in three-dimensional (3D) 1 structure (9 -12). Although this advanced knowledge has been provided for the plant chitin-binding proteins, less is known for the invertebrate chitin-binding proteins including tachycitin (1,(13)(14)(15)(16). Kawabata et al (1) identified that tachycitin is a 73-residues chitin-binding protein having antimicrobial activity.…”
mentioning
confidence: 99%